How and when service quality and satisfaction simultaneously influence purchase intentions? - Yang, Miles; Huang, Y.; Li, S. (The Royal Society of Medicine Press, 2011)
The purpose of this study is to examine how and when service quality and satisfaction simultaneously influence purchase intentions. The study tries to explore and clarify the relationship between service quality and satisfaction, and to examine whether satisfaction simultaneously moderates and mediates the relationship between perceived service quality and purchase intentions. A field survey was conducted for the outpatients of 12 regional hospitals in Taiwan. The findings show that the effects of different dimensions of service quality on purchase intentions are not equal across satisfied and unsatisfied patients. This study provides empirical evidence that show how the dual roles of the moderator and mediator manipulated together by satisfaction, work to affect purchase intentions in hospital settings. In addition, the relationships between service quality and satisfaction are also clarified.